Effect of silver nitrate on some mechanical properties of heat polymerizing acrylic resins (Mustansiria Dental Journal, 2019)
Aim: The aimed study was to evaluate the influence of silver nitrate on surfacehardness and tensile strength of acrylic resins.Materials and methods: A total of 60 specimens were made from heat polymerizingresins. Two mechanical tests were utilized (surface hardness and tensile strength)and 4 experimental groups according to the concentration of silver nitrate used.The specimens without the use of silver nitrate were considered as control. Fortensile strength, all specimens were subjected to force till fracture. For surfacehardness, the specimens were tested via a durometer hardness tester. Allspecimens data were analyzed via ANOVA and Tukey tests.Results: The addition of silver nitrate to acrylic resins reduced significantly thetensile strength. Statistically, highly significant differences were found among allgroups (P≤0.001). Also, the difference between control and experimental groupswas highly significant (P≤0.001). For surface hardness, the silver nitrate improvedthe surface hardness of acrylics. Highly significant differences were statisticallyobserved between control and 900 ppm group (P≤0.001); and among all groups(P≤0.001)with exception that no significant differences between control and150ppm; and between 150ppm and 900ppm groups(P>0.05).Conclusion: The addition of silver nitrate to acrylics reduced significantly the tensilestrength and improved slightly the surface hardness.